Improved Across the Board Access to SARS-CoV-2 Laboratory Testing in an Integrated Medical System; the Veteran Affairs Medical Center (VAMC) Experience - Petersen, J M (Am J Clin Pathol, 2020)
INTRODUCTION/OBJECTIVE: Due to the spread of SARS-CoV-2 – the causative pathogen behind COVID-19, a significant impact on society including significant death, morbidity, strain on the nation’s medical systems, and an economic shutdown of many sectors has come to pass. While society has been affected by this virus, it has also been documented in the mainstream news that this pandemic has disproportionately affected non-white minority groups, and that access to testing for vulnerable populations have been limited. Similarly, previously published epidemiological data by Zuvekas et al. show that populations with health insurance, higher socioeconomic class, and white in race have received significantly better access to private health care resources. As veterans represent a vulnerable population, as part of quality assurance, testing data was reviewed to verify that this trend was not also affecting the VAMC. METHODS: As part of a quality assurance/quality improvement project, a retrospective manual review of all SARS-CoV- 2 RT-PCR tests performed at the VAMC from March 11th, 2020 to April 13th, 2020. These tests were reviewed within the computerized medical record system to determine the age, gender, and ethnicity of the patients. The demographic data from this search was compared with the population statistics of the major metropolitan city that the VAMC is located in. RESULTS: Out of 571 patients who were tested for SARS-CoV-2, 264 (46%) had an ethnic African-Americans background, 135 (24%) had an ethnic Caucasian or white background, 8 had an ethnic Hispanic background, 3 had an ethnic native Hawaiian or other Pacific Islander background, 2 had an ethnic Asian background (0.4%), and 1 had an ethnic American Indian or Alaskan Native background. The rest had left ethnicity unanswered or was unknown/declined to state. The majority of those tested were males (392 or 69%). Ages of patients tested ranged from 24 to 98 years of age. The ethnic distribution of those tested was like the ethnic distribution within the city where the VAMC was located. CONCLUSION: Quality healthcare to the entire population also means that healthcare should be accessible to all members who require it. The VAMC offers broad access for testing to all its patients of all ethnicities. This demonstrates, in the changing healthcare landscape, one of the many advantages of the Veteran Affairs system.